Dual Web-Based Temperature and Humidity Sensing of The Polyculture Fish Cultivation Pond Surface - Abdulhadi, Muhammad; Wicaksono, Arief; Salamah, Khadijah Barorotus; Sugoro, Nirwan (Universitas Sultan Ageng Tirtayasa, 2022)
Cultivating fish in rural areas is one of the efforts to increase food security and the income of its citizens. Every villager can raise consumption and ornamental fish by making ponds in their large yard. Temperature strongly influences Fish cultivation. The high value of temperature fluctuations in the habitat can reduce feeding activity. It also affects the metabolism of the fish larvae. Temperature changes in fish habitats are affected by changes in environmental temperature. Information regarding weather forecasts is very much needed to anticipate environment temperature and humidity changes. In this study, we want to compare the results of temperature and humidity readings by wunderground.com and IoT monitoring devices toward the habitat of Polyculture Fish cultivation Pond. Both show identical temperature patterns had a deviation value is (+2 oC). Meanwhile, both results of humidity measurements appear to be inaccurate, either because they are outside the measurement value or refer to the reference data. Based on monitoring results, both methods can use monitoring the temperature and humidity of the environmental pond.